Diagnostic utility of bronchoalveolar lavage - Sistla Radha (Journal of Cytology, 2014)
Introduction: Bronchoalveolar lavage (BAL) is a diagnostic procedure by which cells and other components from bronchial and alveolar spaces are obtained for various studies. One of the main advantages of BAL is that it can be done as a day care procedure. Material obtained by BAL can give a definite diagnosis in conditions such as infections and malignancies. Aims: The aims and objective of this study were to assess the utility of BAL as a diagnostic tool to determine the diagnostic accuracy of the material obtained from BAL in various infections and neoplastic lesions to study the limitations of BAL in certain lung disorders. Materials and Methods: This study was done in a tertiary care center in Hyderabad. Bronchoscopy was done as an outpatient procedure and lavage fluid obtained analyzed. This is a prospective study done from January 2012 to Jun 2013. Ninety-one BALs were analyzed for total and differential count, microbiological examination and cytological evaluation. Cases selected included nonresolving pneumonias, diffuse lung infiltrates, infiltrates in immunosuppressed hosts and ventilator-associated pneumonias. Results: Bronchoalveolar lavage was done in 91 cases over a period of 1½ years. Definite diagnosis was not given in 7 cases. Four cases were inadequate. Tuberculosis was diagnosed in 22 cases, fungal infections in 7 cases. Thirty-eight cases of bacterial pneumonias were diagnosed, Klebsiella was the most common organism. Malignancy was diagnosed in 13 cases. Conclusion: Definite diagnosis can be made in tuberculosis, fungal infections, bacterial pneumonias and in malignancies.